Analisis Pelaksanaan Program Laboratorium Psikologi Maritim di Kampung Pesisir dalam Menghadapi Tantangan Perubahan Iklim yang Terjadi di Daerah Pesisir Indonesia - Johan Wisnu Saputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Coastal communities are highly dependent on marine natural resources and are therefore vulnerable to the impacts of climate change, both economically and psychologically. Changing weather patterns, sea level rise, coastal erosion, and the uncertainty of the fishing season directly impact the livelihood stability of coastal communities and create ongoing psychological stress. To support coastal community empowerment, Agency X initiated the Kampung Pesisir Program, implemented through various activity clusters. To strengthen the program's effectiveness, a Maritime Psychology Laboratory Program was developed, emphasizing a community-based psychological approach. This study aims to analyze the implementation of the Maritime Psychology Laboratory Program in Kampung Pesisir in addressing the challenges of climate change in Indonesia's coastal areas. The study used a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. Participants included indigenous coastal residents, fishermen, community leaders, student interns, and program managers. The results indicate that coastal communities face structural vulnerability due to dependence on nature, economic constraints, and minimal social protection. The Maritime Psychology Laboratory program serves as a psychosocial space that increases psychological awareness, strengthens community participation, and supports the sustainability of empowerment programs amidst the challenges of climate change.